DETERMINANTS AFFECTING THE SUCCESS OF DISTRIBUTION GRID PROJECTS IN BINH THUAN POWER COMPANY VIETNAM - Pham Van Tai & Le Duc Thu (International Journal of Research Science and Management, 2017)
The research identified the critical factors affecting the success of the distribution grid project in Binh Thuan Power Company, clarify the mutual relationship between the critical factors affecting the success of the distribution grid project in Binh Thuan Power Company and recommended and rated the solution to enhance the success of the distribution grid project in Binh Thuan Power Company. The research had found fours critical factors: External factors of project, Controlling and coordination factors, Characterictis of project, Competences of participants involved in the project. The regression results show that four groups of factors that are positively related to the success of the project and there is a statistically significant. Including theory and practice, the group highlights the impact factor is External factor of project and Controlling and coordination factors. The study results contribute theoretically about project management in Binh Thuan Power Company. The project manager at Binh Thuan Power Company manage effectively to enhance the likelihood of success of the project.